Environmentally Sustainable Development through Stakeholder Engagement in Developed and Emerging Countries. (4th March 2014) - Dögl, Corinna; Behnam, Michael
Abstract This cross‐country study investigates the antecedents and outcomes of corporate environmental responsibility (CER) practices in developed and emerging countries. Based on stakeholder and institutional theory, we conducted an empirical study among firms in Germany, USA, India and China. We found support for a significant positive relationship between regulatory, market and social stakeholder influences, CER practices and business outcomes in the total and individual country samples. Regarding country differences, our data reveal significant similarities and differences between developed and emerging countries. Market stakeholder influences are stronger in developed countries, whereas regulatory and social stakeholder influences do not differ significantly between the two country groups. The relationship between CER practices and positive business outcomes is stronger in emerging than in developed countries. Implications for institutional theory and organizations are outlined. Copyright © 2014 John Wiley & Sons, Ltd and ERP Environment